2001
DOI: 10.1097/00005373-200105000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients Using a Tiered Trauma Response Protocol

Abstract: Implementation of the tiered response protocol led to a substantial change in the operational response in the emergency department. Although processes of care were nominally prolonged, adverse consequences were not identified. We concluded from this quality improvement review that implementation of a tiered response protocol was satisfactory and improved efficiency. Further work is required to improve accuracy of the categorization of trauma system patients as either MOD or FULL trauma codes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…Furthermore, the lower mortality rate and the shorter intensive care unit length of stay in the undertriaged patients likely reflect the significantly lower ISS and higher GCS in this population. This finding is similar to other studies that seek to find factors related to undertriage 28,29. Undertriaged patients tend to have lower injury scores than TTA patients, and thus are expected to have better outcomes overall.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the lower mortality rate and the shorter intensive care unit length of stay in the undertriaged patients likely reflect the significantly lower ISS and higher GCS in this population. This finding is similar to other studies that seek to find factors related to undertriage 28,29. Undertriaged patients tend to have lower injury scores than TTA patients, and thus are expected to have better outcomes overall.…”
Section: Discussionsupporting
confidence: 88%
“…Using several response levels, multispecialty teams (when severe injuries and abnormal vital signs are identified), and smaller teams for stable trauma patients promote better resource utilization [37]. In patients with minor to moderate injury, rapid trauma workup is still important, as occult injuries may exist, but it may still not mandate a full trauma team.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors, with smaller numbers of patients, have also reported success with similar systems. Eastes et al 7 compared patient outcomes for a 2-year period before and after establishing a two-tier team response and compared these data with a case-control group who had been undertriaged. They used 10 physiologic and anatomic factors in the triage decision.…”
Section: Discussionmentioning
confidence: 99%